Describing social stigma of disability’s family through circumplex model on film - Trihastuti, Maria Claudia Wahyu; Marta, Rustono Farady; Panggabean, Hana; Fernandes, Maristela Julia (Jurnal Studi Komunikasi, 2022)
The biographical film, Zero to Hero, shows the true story of Hong Kong sprinter So Wa Wai who won the 1996-2008 Paralympic Olympics. This study aims to identify signs to build meaning based on speech (words), images, images and sounds, words and gestures/body language, images and gestures/body language, images and objects, and words and objects. Identification of the mother's role in controlling the balance of the dimensions of cohesion, and flexibility through the application of effective communication with family members and the community is illustrated in this study. Dimensions of cohesion and flexibility that is based on Olson's Circumplex model describing family functions. Parenting interactions through the communication dimension of the mother figure play an important role in the Circumplex model. The analytical method used is Umberto Eco's semiotics which relies on the constructivism paradigm. The results showed that the Zero to Hero film contains three meaningful signs based on Olson's Circumplex model, namely signs in the form of speech, speech and body language, and speech and objects.